A high-energy sodium-ion capacitor enabled by a nitrogen/sulfur co-doped hollow carbon nanofiber anode and an activated carbon cathode. Issue 2 (16th November 2018) - Liao, Ke; Wang, Huanwen; Wang, Libin; Xu, Dongming; Wu, Mao; Wang, Rui; He, Beibei; Gong, Yansheng; Hu, Xianluo
Abstract : Hierarchically nanostructured N/S-co-doped hollow carbon nanofibers are fabricated as anodes for high-energy Na-ion capacitors. Abstract : Nonaqueous Na-ion capacitors (NICs) have been recently regarded as potential sustainable power devices due to their high specific energy/power and the abundant distribution of sodium resources on the Earth. However, the power performance of current NICs is usually restricted by the kinetics imbalance between sodium deintercalation/intercalation in the anode and surface ion adsorption/desorption in the cathode. Herein, we demonstrate superior sodium-ion storage properties of nitrogen/sulfur co-doped hierarchical hollow carbon nanofibers (N/S-HCNFs) for their application as an ideal anode material for NICs. The N/S-HCNFs are fabricated through in situ gas sulfuration of a hollow polyaniline nanofiber precursor, which is obtained with the aid of citric acid templates. Benefiting from the positive synergistic effects of both N and S co-doping in carbon and the hierarchical hollow one-dimensional structure, the sodium-storage performance of N/S-HCNFs half-cell versus Na/Na + exhibits a high capacity (∼447 mA h g −1 at 50 mA g −1 ), excellent rate capability (∼185 mA h g −1 at 10 A g −1 ), and outstanding cycling stability (no capacity decay after 3000 cycles at 5 A g −1 ), which is among the best sodium-ion storage performances of carbonaceous Na-storage anodes. Furthermore, a dual-carbon NIC device is constructed with N/S-HCNFs as an anode and activated carbon (AC) as a cathode, and it has a large energy density of 116.4 W h kg −1, a high power density of 20 kW kg −1 (at 48.2 W h kg −1 ) and a long cycle life of 3000 cycles, which is superior to most reported AC-based NICs.